The analysis of Modified Qing’ E Formula on the differential expression of exosomal miRNAs in the femoral head bone tissue of mice with steroid-induced ischemic necrosis of femoral head - Zhu, Wei; Zhang, Faxue; Lu, Junjie; Ma, Chen; Shen, Lin; Hu, Desheng; Xu, Xiaojuan; Shuai, Bo (Frontiers in Endocrinology, 2022)
Objective: To investigate the differential expression of exosomal miRNAs in the bone marrow tissue of Modified Qing’ E Formula (MQEF) on steroid-induced ischemic necrosis of the femoral head (INFH) model. Methods: Steroid hormones were used to establish the INFH model and treated with MQEF. After successful modeling, femoral tissue exosomes were isolated for miRNA sequencing to obtain femoral tissue exosomal differential miRNAs. By GO and KEGG analysis of the differential genes in both groups, the major exosomal miRNAs of MQEF exerting anti-INFH as well as the major signaling pathways were identified. Next, a quantitative metabolomic validation of MQEF with broad targeting was performed to obtain the main active components of MQEF and to perform biological analysis and signaling pathway prediction of the active components by network pharmacology. Finally, the sequencing results were validated by using RT-qPCR. The results of miRNA sequencing were verified by double examination of network pharmacology and RT-qPCR, and the exosomal miRNAs regulated by the anti-INFH effect of MQEF and the specific signaling pathway of the effect were clarified. Results: A total of 65,389 target genes were predicted in the exosomes of two groups, and 18 significant differentially expressed miRNAs were obtained, of which 14 were up-regulated and 4 down-regulated. GO enrichment analysis showed that these predicted target genes were enriched in 12371 biological processes, 1727 cell components, and 4112 molecular functions. KEGG analysis showed that the predicted miRNA target genes were annotated to 342 signal pathways, in which the highly enriched pathways closely related to bone metabolism were PI3K-Akt signal pathway, MAPK signal pathway, and Wnt signal pathway. The most significantly up-regulated miRNAs were miR-185-3p and miR-1b-5p and the most significantly down-regulated miRNAs were miR-129b-5p and miR-223-5p, of which the targeted genes were closely related to the PI3K-Akt signal pathway. Real-time quantitative PCR validation showed that miR-185-3p was up-regulated 7.2-fold and miR-129b-5p was down-regulated 2.2-fold in the treatment group, and the difference was significant (P < 0.05). Conclusions: MQEF can regulate exosomal miRNA expression in steroid-induced INFH models, miR-185-3p or miR-129b-5p/ PI3K-Akt signal axis may be part of the mechanism of MQEF against steroid-induced INFH.